Comparison of Coronal Hole and Quiet-Sun Chromosphere Using IRIS Mg ii h and k Observations of Polar Off-limb Regions - Akiko Tei; Stanislav Gunár; Takenori J. Okamoto (The Astrophysical Journal)
Solar quiet regions are divided into coronal hole regions (CH) and quiet-Sun regions (QS). The global magnetic field in CH is considered open to interplanetary space, while that in QS is closed. To constrain the solar atmosphere and solar wind model, we statistically compared CH and QS in the chromosphere by quantitatively analyzing all available high-resolution spectral data sets of polar off-limb regions taken from the entire catalog of the Interface Region Imaging Spectrograph (IRIS) satellite. We extracted the characteristic quantities from the Mg ii h and k line profiles and compared the dependence of those quantities on the height from the photospheric limb. The main findings are as follows. First, the integrated intensities in the Mg ii k line show a steeper decrease with height in QS while they remain bright at higher altitudes in CH. Second, the unsigned line-of-sight velocities in the Mg ii k line generally increase with height in both regions, although the unsigned velocities increase with height more strongly in QS than in CH. Third, the Mg ii k line widths increase just above the limb and then decrease with height in both CH and QS, but are overall larger for CH than for QS, especially at the lower altitudes. Finally, we found the ratio of the Mg ii k and h lines to show a two-step increase with height in both regions. The results suggest the spicules are higher in CH, and the CH chromosphere exhibits faster motions than the QS.